If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2x + -5)(5x + 2) = 0 Reorder the terms: 2x(-5 + 2x)(5x + 2) = 0 Reorder the terms: 2x(-5 + 2x)(2 + 5x) = 0 Multiply (-5 + 2x) * (2 + 5x) 2x(-5(2 + 5x) + 2x * (2 + 5x)) = 0 2x((2 * -5 + 5x * -5) + 2x * (2 + 5x)) = 0 2x((-10 + -25x) + 2x * (2 + 5x)) = 0 2x(-10 + -25x + (2 * 2x + 5x * 2x)) = 0 2x(-10 + -25x + (4x + 10x2)) = 0 Combine like terms: -25x + 4x = -21x 2x(-10 + -21x + 10x2) = 0 (-10 * 2x + -21x * 2x + 10x2 * 2x) = 0 (-20x + -42x2 + 20x3) = 0 Solving -20x + -42x2 + 20x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-10 + -21x + 10x2) = 0 Factor a trinomial. 2x((-2 + -5x)(5 + -2x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + -5x)' equal to zero and attempt to solve: Simplifying -2 + -5x = 0 Solving -2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 0 + 2 -5x = 0 + 2 Combine like terms: 0 + 2 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4Subproblem 3
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {0, -0.4, 2.5}
| 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 | | 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 | | -8u+2(u+5)=16 | | 2x+3-5=5x-3+3x | | 7-4x=5x | | 2y+3(y-2)=29 | | C=240+0.75Y | | 3(x+4)=2(11-x) | | -2=6(x+3)-2x | | 284=-66a | | 4x^2+2x+1=o | | 2x-2=11-4x | | (X-5)^5/3-73=170 | | 10^6/10^2= | | n+1.2=7.4 | | Tan(28)=x/32 | | 4c-39=43c-78 | | 3(7+3x)=30 | | 5/3m=5/9 |